2006
DOI: 10.1191/0960327105ht627oa
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chromium on vertebrae, femur and calvaria of adult male rats

Abstract: Alloys of chromium have a long history of success in the surgical treatment of many orthopaedic defects. Nonetheless, prostheses loosening are commonly found around arthoplasties due to corrosion of metals. On this basis, it is hypothesized that chromium accumulation interferes with remodeling of bone. The present study aims to analyse the toxic effects of chromium on bone phosphatases in various regions of the bone in rats. Rats were treated with chromium intraperitoneally (0.5 mg/kg) in the form of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
1
12
0
1
Order By: Relevance
“…Brzóska et al [42,43] indicated that low exposure to cadmium (Cd) may affect the mineralization and biomechanical properties of growing bone, thus increasing the risk of fractures. Sankaramanivel et al[44] revealed that a significant increase in the concentration of Chromium can decrease bone formation rate. Benzo(a)pyrene (BaP) and 7,12-dimethylbenz(a)anthracene (DMBA) are polycyclic aromatic hydrocarbons (PAHs) found in the tar fraction of cigarette smoke.…”
Section: Discussionmentioning
confidence: 99%
“…Brzóska et al [42,43] indicated that low exposure to cadmium (Cd) may affect the mineralization and biomechanical properties of growing bone, thus increasing the risk of fractures. Sankaramanivel et al[44] revealed that a significant increase in the concentration of Chromium can decrease bone formation rate. Benzo(a)pyrene (BaP) and 7,12-dimethylbenz(a)anthracene (DMBA) are polycyclic aromatic hydrocarbons (PAHs) found in the tar fraction of cigarette smoke.…”
Section: Discussionmentioning
confidence: 99%
“…For histologic scoring of inflammation and bone erosion, sections were stained with either hematoxylin and eosin or tartrate‐resistant acid phosphatase (TRAP). For TRAP staining, sections were incubated in 0.1 M Tris HCl, pH 9.0, for 18 hours, followed by 0.1 M sodium citrate, pH 5.2, for 3 hours (23). Activated sections were incubated for 30 minutes at 37°C in 0.005% Napthol AS‐MX phosphate (Sigma)/0.01% N , N ‐dimethylformamide/0.03% Fast Red Violet LB salt (Sigma)/50 m M sodium tartrate in 0.1 M acetate, pH 5.0 (24, 25) and counterstained with hematoxylin.…”
Section: Methodsmentioning
confidence: 99%
“…Research carried out to-date has shown only negative effects with regard to hexavalent chromium administration [8], yet trivalent chromium administered by gavage as an inorganic salt or an organic complex is considered to be non-toxic for rats, with LD 50 > 2,000 mg/kg BW [11]. In the experiment undertaken by De Lucca et al [12] involving juvenile rats, in which hexavalent chromium was given as 6.25 and 12.5 mg/kg/10 days dosages, toxic effects were noticed on bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, while there is little information about long-term exposure to the trivalent form, hexavalent chromium overload is known to modify the natural bone metabolism, especially bone formation and resorption, thus having an effect on skeletal growth and condition [4][5][6][7]. These influences may have rebound as changes to some parameters, among these being density and quality of bone [8]. Such effects may be measured tomographically and densitometrically.…”
Section: Introductionmentioning
confidence: 99%